An integrated model of the adoption of radio frequency identification technology in the hotel industry. (2018) - Pool, Javad Khazaei; Doosti, Shabnam; Tabaeeian, Reihaneh Alsadat; Mortazavi, Marjan
Radio frequency identification (RFID) represents a brand new technology that promises to improve process efficiency in hospitality settings. The technology-organisation-environment (TOE) framework and technology acceptance model (TAM) are applied to gain insights into influences on the adoption intention of RFID in the hotel industry. By adopting the TOE framework and TAM as a theoretical base, this descriptive-survey study used questionnaire to collect data in 92 different hotels in Iran. The proposed research model is tested against using structural equation modelling (SEM). The results showed that TOE framework and TAM have positive effects on intentions to use RFID. Our results support the proposed conceptualisation and shed significant and useful insights on the key factors associated with hotels' adoption of RFID.